PENGARUH ETIKA, KOMITMEN ORGANISASI DAN PENEKANAN ANGGARAN TERHADAP BUDGETARY SLACK (STUDI PADA OPD KAB. KEPAHIANG) - Muhammad Egi Etalariksyah; Ummul khair (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze the influence of intellectual capital, market value, and institutional ownership on firm value in LQ45 companies listed on the Indonesia Stock Exchange (IDX) for the period 2018–2022. The research method used is quantitative with an associative approach. The data used are secondary data obtained from the companies' financial reports. The sampling technique used was purposive sampling, resulting in 92 observations after removing outliers. Data analysis was performed using multiple linear regression with IBM SPSS through the classical assumption test, partial t-test, simultaneous t-test (F-test), and coefficient of determination (R²). The results show that intellectual capital has a significant influence on firm value, while market value and institutional ownership have no effect. Simultaneously, intellectual capital, market value, and institutional ownership have a significant influence on firm value. The conclusion of this study shows that increasing intellectual capital can increase company value, while market value and institutional ownership have not been able to provide a significant influence on company value in LQ45 companies listed on the Indonesia Stock Exchange for the 2018–2022 period. Keywords: Earnings Per Share; Intellectual Capital; Institutional Ownership; Firm Value; Price to Book Value